US AND DOPPLER-GUIDED SURGICAL TREATMENT BASED ON IMMUNOHISTOCHEMICAL FINDINGS IN MIDPORTION ACHILLES TENDINOPATHY SHOWS GOOD CLINICAL RESULTS AND FAST RETURN TO ACTIVITY. Issue 9 (10th May 2013) - Alfredson, H; Andersson, G; Backman, L; Bagge, J; Danielson, P; Forsgren, S
Abstract : Introduction: Treatment of midportion Achilles tendinopathy has been known to be difficult. Recent ultrasound(US) and Doppler(CD) findings (high blood flow outside ventral tendon), together with results of immunohistochemical analyses (marked presence of blood vessels accompanied by nerve fascicles in the ventral peritendinous tissue) have led to new treatment approaches like sclerosing polidocanol injections, where US and CD-guided injections in the region with high blood flow and nerves outside the tendon have shown good results. However, for satisfying pain relief multiple injection treatments were often needed. Therefore, based on the same principles as for the sclerosing injections, a more radical and one stage mini-surgical procedure has been invented. Methods: 107 patients (66 men, 41 women), mean age 43 years (range 24–77), with tendinosis in 125 Achilles tendons were, in local anaesthesia, treated with a US+CD-guided new surgical approach outside the ventral tendon. Pain during tendon loading activity (VAS) and satisfaction with treatment, were evaluated. Results: Before surgery, the mean VAS was 77. After surgery (follow up mean 18 months, range 6–33) the mean VAS was 2 in 111 tendons (89%) from satisfied patients back in full Achilles tendon loading activity. Conclusions: US+CD-guided scraping/tenolysis in the region with rich vascularity and innervation outside the ventral tendon shows good short term clinical results in midportion Achilles tendinopathy.